2013
DOI: 10.1111/jifm.12005
|View full text |Cite
|
Sign up to set email alerts
|

A Respecified Fama French Three‐Factor Model for the New European Union Member States

Abstract: This study uses factor models to explain stock market returns in the Eastern European (EE) countries that joined the European Union (EU) in 2004. In line with other studies, we find that the market value of equity component in the Fama French (1993) three‐factor model performs poorly when applied to our emerging markets dataset. We propose a significant amendment to the standard three‐factor model by replacing the market value of equity factor with a term that proxies for accounting manipulation. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…14 We base our choice of the dependent variable on its ease of interpretation, as well as documented use both in financial analyses and academic research (e.g. Fama and French 1993, 2015Foye andMramor 2013, 2016). The extant literature also highlights P/E's utlisation among other commonly-used multiples such as price-to-earnings or price-to-sales ratios (as well as metrics based on cash flow, such as enterprise value relative to earnings before interest and taxes) in firm market valuation (see especially Lie and Lie 2002, Fama and French 2002, and Cheung et al 2009.…”
Section: Hypothesis 2: Effects Of Informal Institutions On Firm Vmentioning
confidence: 99%
“…14 We base our choice of the dependent variable on its ease of interpretation, as well as documented use both in financial analyses and academic research (e.g. Fama and French 1993, 2015Foye andMramor 2013, 2016). The extant literature also highlights P/E's utlisation among other commonly-used multiples such as price-to-earnings or price-to-sales ratios (as well as metrics based on cash flow, such as enterprise value relative to earnings before interest and taxes) in firm market valuation (see especially Lie and Lie 2002, Fama and French 2002, and Cheung et al 2009.…”
Section: Hypothesis 2: Effects Of Informal Institutions On Firm Vmentioning
confidence: 99%
“…Other works (Kothari et al, 1995;Daniel and Titman, 1997;Davis et al, 2000;Taneja, 2010;Manjunatha and Mallikarjunappa, 2011;Eraslan, 2013;Foye et al, 2013;Sehgal and Balakrishnan, 2013;Sharma and Mehta, 2013) show that:…”
Section: Literature Reviewmentioning
confidence: 97%
“…This issue is, however, debatable. For example, Foye, Mramor, and Pahor (2013) analyzed the new European Union members and found that the model of Fama and French (1993) has some serious disadvantages in such a context. Thus, some researchers have proposed modifications.…”
Section: Literature Reviewmentioning
confidence: 99%